Kehidupan Muslim di Myanmar Sebelum dan Sesudah Kemerdekaan - Nur Anisah Hasibuan; Erasiah; Lukmanul Hakim (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
This paper discusses the development of the History of Islamic Civilization in Myanmar before and after independence. This discussion is relevant because the Muslim community in Myanmar has been the focus of world attention in recent decades. Their challenging living conditions have come under the spotlight, especially as various issues related to Muslims in Burma (Myanmar) have emerged. Discrimination against them often occurs because they are a minority in a country where the majority of the population is non-Muslim. The living conditions of Muslims in Myanmar create complex dynamics and are interesting to discuss. This paper draws its sources from library research, with the aim of exploring the dynamics of Myanmar Muslim life through a historical lens. The data collection method involves referencing literature, including books, journals, and other scholarly papers. The data analysis process involves collecting, identifying and categorizing information, which is then interpreted to form concepts that support the main discussion in this paper. The results show that Islam has been present in Myanmar since the 9th century. Various tribes or ethnicities in Myanmar embrace Islam, such as the Rohingya, Huihui (Panthay), Burmese Muslims, Muslims of Indian descent, and Zerbadi. The Rohingyas in particular are known as a group that is against the Myanmar government. This has led them to be regarded as rebels, resulting in the persecution of the Rohingya.